2013
DOI: 10.3844/erjsp.2013.15.23
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Utilising Renewable Energy Options Into the Libyan Energy Mix

Abstract: This study is to investigate the financial and technological challenges and opportunities facing the utilisation of renewable energy resources in Libya. The work investigates the availability of different renewable energy resources in Libya and the practicality of implementing some of these options. The study aims to study and identify the contribution of renewable energy in the mixture of total energy supply in Libya. It also investigates the essential legislation in the field of energy, which contributes to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…Consequently, there is an urgent need for comprehensive energy strategies in renewable-energy technology [15]. Mohamed et al [16,17] reported that by the end of the year 2020, the projected demand for electrical power would be more than two and half. Renewable energy could be the effective solution for the increased energy demand.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, there is an urgent need for comprehensive energy strategies in renewable-energy technology [15]. Mohamed et al [16,17] reported that by the end of the year 2020, the projected demand for electrical power would be more than two and half. Renewable energy could be the effective solution for the increased energy demand.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows the average wind speed for different cities in Libya. Previous research (Mohamed MAA et al, 2013) reported that the possibility of utilizing wind energy in electricity generation in some locations and connecting it with the nation grid is high as in case of Benina, Sirt, Dernah, Sebha, and Tolmetha, whereas in other areas such as Ejdabia and Sorman it is more favorable to use wind energy for water pumping and other applications. Wind energy potential for electricity production has not started yet.…”
Section: Wind Energy Potential In Libyamentioning
confidence: 99%
“…Thus, Libya plays a major role in providing petroleum and electricity to international networks [2]. Electricity generation between the years of 2000 and 2010 has been doubled in Libya.…”
Section: For Example Desertec Was Developed By the Trans-mediterranementioning
confidence: 99%
“…In this regard, generaly most months in Libya are hot with a mean temperature exceeding 35°C in Eastern regions and could reach over 50°C in the south during the hottest months of the year. Likewise in winter, the temperature could fall below 0°C and this is associated with a high rate of electricity consumption [2,50]. The fact that the government heavily subsidises current consumption cost is leading to rapid energy demand with customers paying one-third of the cost per kWh [2][3].…”
Section: Electricity Demand and Load Variation In Libyamentioning
confidence: 99%
See 1 more Smart Citation